Factors Affecting the Implementation of Traditional Health Services at the Health Center In South Sorong Regency in 2024 - Sumbung, Agustina; Uly, Nilawati; Al-Maidin, Achmad R. Muttaqien; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: The Indonesian government is committed to strengthening traditional health services by integrating them into the National Health System to enhance accessibility and cultural relevance. Objective: This study aimed to identify key factors influencing the implementation of traditional health services at health centers (Puskesmas) in South Sorong Regency in 2024. Methods: A quantitative research design was used to analyze the influence of human resources, disposition, bureaucratic structure, community support, and communication on service implementation. Data analysis included validity and reliability tests, Kruskal-Wallis test, T-tests, F-tests, and multiple linear regression. Results: All five factors significantly influenced the implementation of traditional health services, both partially and simultaneously (p = 0.000 < 0.05). The model showed high reliability (Cronbach’s Alpha = 0.821) and a coefficient of determination (R²) of 0.999, indicating that these variables explained 99.9% of the variation in implementation. Conclusion: Human resources, disposition, bureaucratic structure, community support, and communication significantly affect the implementation of traditional health services at health centers. Enhancing these factors is essential for improving the effectiveness and sustainability of traditional health programs in the region.